Flow characteristics of distinctly viscous multilayered intestinal fluid motion - Pandey S.K.; Chaube M.K.; Tripathi D. (My University, 2025)
The goal of this investigation is to study the three layered (core layer, intermediate layer, and peripheral layer) tubular flow of power law fluids with variable viscosity by peristalsis in order to investigate the strength of the role played by an artificially generated intermediate layer to ease constipation.The solution is carried out under the long wavelength and low Reynolds number approximations in the wave frame of reference as the flow is creeping one.The stream functions for each layer such as core layer, intermediate layer, and peripheral layer are determined.The expressions for axial pressure gradient, interfaces, trapping, and reflux limits are obtained. The effects of power law index and viscosities on pressure across one wavelength, mechanical efficiency, and trapping are discussed numerically. It is found that the pressure required to restrain flowrates and the mechanical efficiency increase with the viscosities of the intermediate and peripheral layers as well as with the flow behaviour index. It is observed that the axisymmetric flow in intestines is less prone to constipation than two-dimensional flow and may be more easily overcome with introducing a viscous intermediate layer. © 2015 S. K. Pandey et al.